2020
DOI: 10.5339/qmj.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Venous–arterial CO2 difference in children with sepsis and its correlation with myocardial dysfunction

Abstract: Objective: This study aimed to determine the association between venous–arterial CO2 difference (Pv-aCO2) and clinical outcomes of interest in children with severe sepsis and septic shock. Design: An analytical observational study of a prospective cohort was conducted. Setting: The study was carried out from January 2015 to January 2018 in the pediatric intensive care unit of a referral hospital. Materials and methods: Of a total of 1159 patients who were admitted to pediatric critical care, 375 had severe sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…However, in this study, the correlation between cardiac index measured by thermodilution and ∆CO 2 was weak (r = 0.25, p < 0.01). In pediatric patients with severe sepsis, Fernández-Sarmiento et al also found no correlation between ejection fraction measured by transthoracic echocardiography and ∆CO 2 (r = 0.13) 11 . In contrast, in a group of adult cardiovascular surgery patients, Takami and Masumoto found a moderate correlation between cardiac index and ∆CO 2 (r = 0.35, p < 0.001) and between venous saturation and ∆CO 2 (r = 0.35, p < 0.001) 10 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in this study, the correlation between cardiac index measured by thermodilution and ∆CO 2 was weak (r = 0.25, p < 0.01). In pediatric patients with severe sepsis, Fernández-Sarmiento et al also found no correlation between ejection fraction measured by transthoracic echocardiography and ∆CO 2 (r = 0.13) 11 . In contrast, in a group of adult cardiovascular surgery patients, Takami and Masumoto found a moderate correlation between cardiac index and ∆CO 2 (r = 0.35, p < 0.001) and between venous saturation and ∆CO 2 (r = 0.35, p < 0.001) 10 .…”
Section: Discussionmentioning
confidence: 96%
“…Decreased tissue blood flow (ischemic hypoxia) is associated with venous hypercapnia due to cellular anoxia resulting in increased CO 2 production 11 . The increase in arterial CO 2 depends on gas exchange and, because it is very efficient at the alveolar level, it is not significantly affected by decreased pulmonary flow.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the pediatric population are scarce and showed promising but conflicting results. A recent pediatric study in children with septic shock failed to detect a clear association between higher ∆PCO 2 and CO measures [75].…”
Section: Clinical Use Of ∆Cco 2 and ∆Pcomentioning
confidence: 92%
“…No se han demostrado diferencias referentes a su monitorización en forma continua o intermitente en pacientes pediátricos con shock séptico 48 ni tampoco se ha visto asociación con la detección de falla multiorgánica 49 . Importantemente, un valor normal no descarta la existencia de alteración en la perfusión tisular dado que esto puede determinar una menor extracción de oxígeno 39 (Figura 3).…”
Section: Saturación Venosa Central De Oxígeno (Svco 2 )unclassified